FTIR spectroscopic analysis of soil in forensic science - Force, Jaden; Elkins, Kelly M. (Frontiers in Analytical Science, 2025)
Soil is a complex mixture of organic matter and inorganic materials of varying sizes including sand, minerals, salts, and clay. Soil may also contain heavy metals based upon the pH and the use of the land including mining, tanning, and other industrial activities. Spectroscopic tools can be used to assess the metal ion complexation and bridging of natural organic matter (NOM) and chemical moieties of the NOM. Attenuated total reflectance (ATR) FTIR spectroscopy can be used to characterize soils toward forensic geolocation. Soils have been found to have unique vibrational spectral fingerprints as NOM structure, makeup, pH, and bound metals and materials can aid in individualizing the soils. The focus of this review is the application of Fourier transform infrared spectroscopy (FTIR) for the forensic analysis of soils. It provides an overview of the sampling process, locations, collection and homogenization, instrumental settings, and data analysis groups have used in their studies. Different soils have been found to have unique vibrational spectral fingerprints and FTIR has been shown to characterize soils for forensic geolocation. The review captures the approaches and findings across the field and will be informative to guide the future direction and methods for ongoing research. A standardized and consensus approach for sampling, preprocessing and data collection would accelerate data comparisons and conclusions that can be made from soil investigations and applications to casework.